Corvid interference with Canid Pest Ejectors in the southern rangelands of Western Australia - Kreplins, T.; Kennedy, M.; Dundas, S.; Adams, P.; Bateman, Bill; Fleming, P. (Wiley-Blackwell Publishing Ltd, 2018)
Canid Pest Ejectors (CPE) are a method of population management that has recently been approved for the control of wild dogs and foxes in Australia. A pilot trial of CPEs (n = 10) targeting wild dogs was conducted in the southern rangelands of Western Australia in the winter of 2017. CPEs were deployed for 81 days, which included periods of significant rainfall. CPEs were not serviced during deployment, which is a likely situation for remote areas where access may be limited. During deployment, all ejector units corroded and plastic capsules containing 1080 degraded (but did not leak). For CPEs to remain effective in the field, they require regular inspections and servicing, particularly in wet conditions. Interference by nontarget corvid species was observed. Six CPEs were interfered with by corvids, with the lures removed from three, partially removed from another two and one disassembled. Our data suggest that corvid interference with ejectors may have a significant impact on the efficiency and safety of their use. Further investigation into the usefulness of Canid Pest Ejectors as method of canid control is required for rangeland use.